Association of health-risk behaviors and depressive symptoms and anxiety symptoms: a school-based sample of Chinese adolescents. (22nd October 2019) - Luo, Xiaomin; Zhou, Yu; Zheng, Ruimin; Li, Xin; Dai, Yue; Narayan, Anuradha; Huang, Xiaona; Tian, Xiaobo; Jin, Xi; Mei, Lili; Xie, Xinyan; Gu, Huaiting; et al.
Abstract: Background Depressive symptoms and anxiety symptoms of adolescents not only affect youth but also have wide-ranging impacts on the health of adults. The study was carried out to determine the epidemiological characteristics of depressive symptoms and anxiety symptoms and the associations between the two and health-risk behaviors in Chinese adolescents. Methods Participants were recruited from the junior and senior high schools in China. Data were collected by self-designed questionnaires. The questionnaires included questions about demographic characteristics, depressive symptom scales, anxiety symptom scales and nine categories of health-risk behaviors. Descriptive analysis and binary logistic regression were performed by SPSS 21.0 software. Results There were 4.4% of the participants with depressive symptoms. Approximately 32.0% of the participants had anxiety symptoms. Girls and general senior school students were risk factors for depressive symptoms and anxiety symptoms. Multiple health-risk behaviors were associated with depressive symptoms and anxiety symptoms in Chinese adolescents. Conclusion Depressive symptoms and anxiety symptoms were prevalent in Chinese adolescents. Their distribution was affected by certain health-risk behaviors. Multiple health-risk behaviors were associated with depressive symptoms and anxiety symptoms in Chinese adolescents.